Sharia-Compliant Digital Satisfaction: Linking Self-Service Technology and Islamic Bank Loyalty - Prades Ariato Silondae; Muhammad Wahyuddin Abdullah; Sudirman Sudirman; Adwi Adwi (Research Horizon, 2026)
Drawing on technology acceptance logic, Islamic service quality, expectation-confirmation reasoning, and relationship marketing, the study proposes that loyalty in Islamic digital banking emerges from the convergence of technological value and sharia-based service legitimacy. This study examines how self-service technology and Islamic service quality shape customer loyalty through customer satisfaction in Islamic banking. A quantitative explanatory design was used, involving 96 customers of Bank Syariah Indonesia in Kendari City, Indonesia. Data were analyzed using partial least squares structural equation modeling with SmartPLS 4. The findings show that self-service technology and Islamic service quality positively influence customer satisfaction and loyalty, while customer satisfaction also positively influences loyalty. Customer satisfaction partially mediates the effects of both self-service technology and Islamic service quality on loyalty. Self-service technology emerges as the strongest driver of customer satisfaction, indicating that digital banking convenience, security, transparency, accountability, and Sharia compliance are central to customer evaluations. The theoretical contribution of this study lies in advancing the concept of sharia-compliant digital satisfaction, which extends technology acceptance, Islamic service quality, and relationship marketing perspectives by explaining customer loyalty as a value-based outcome of digital service experience, Islamic legitimacy, and maslahah-oriented satisfaction.